Improving Mathematics Screening in Middle School. Issue 4 (1st December 2019) - Klingbeil, David A.; Maurice, Samuel A.; Van Norman, Ethan R.; Nelson, Peter M.; Birr, Chris; Hanrahan, Amanda R.; Schramm, Amber L.; Copek, Rebecca A.; Carse, Sara A.; Koppel, Rachael A.; Lopez, Abigail L.
Abstract: Common universal screening methods for determining math risk in middle school grades may not result in optimal diagnostic accuracy. We evaluated current screening practices and several potential modifications for predicting math proficiency on an end-of-year state test in a suburban school district. Previously, the district used the Measures of Academic Progress (MAP) to determine student risk in fall. Creating local cut scores for the preceding-year state test scores and the MAP resulted in the most accurate and efficient methods of assessing risk. Multiskill computation and application curriculum-based measures added little relative value to the combination of MAP and preceding-year state test scores. Results suggest schools could improve their screening practices by first evaluating their current procedures and, if unacceptable, determining whether local cut scores provide the desired improvements to accuracy before considering the adoption of additional measures.